The rise of Africa's middle class Myths, realities and critical engagements - Melber, Henning (Africa Now, 2016)
Across Africa, a burgeoning middle class has become the poster child for the 'Africa rising' narrative. Ambitious, aspirational and increasingly affluent, this group is said to embody the values and hopes of the new Africa, with international bodies ranging from the United Nations Development Programme to the World Bank regarding them as important agents of both economic development and democratic change. This narrative, however, obscures the complex and often ambiguous role that this group actually plays in African societies. Bringing together economists, political scientists, anthropologists and development experts, and spanning a variety of case studies from across the continent, this collection provides a much-needed corrective to the received wisdom within development circles, and provides a fresh perspective on social transformations in contemporary Africa.